Allergy to cow’s milk protein: knowledge of caregivers (Research, Society and Development, 2022)
Objective: It is to evaluate the knowledge of caregivers of children diagnosed with CMPA about dietary restrictions, and to verify if these caregivers know how to identify the different nomenclatures that indicate the presence of cow's milk protein. Methodology: This is a cross-sectional, quantitative study, with an interview through a telephone approach to 102 parents or caregivers of children diagnosed with Cow's Milk Protein Allergy assisted by the Special Milk Program of the City of Belém/PA. For statistical analysis, Bio Estat 5.0, Chi-square tests, G test (Adherence), Spearman's correlation test and Multiple Linear Regression were adopted. (p≤0.05). Results: 51% of those studied had three or more consultations with health professionals, 55% received guidance from Doctors and Nutritionists. 83% of the guidelines extended to reading the labels. Among the nomenclatures that indicate the presence of milk protein, only Lactose and Whey Protein showed significant responses. There was no significant difference between the declared responses on the exclusion diet. Regarding the knowledge of the symptoms developed by the APLV, all the answers showed significance in the knowledge of the gastroenteral, respiratory, cutaneous manifestations, and anthropometric symptoms. When questioned about the danger of preparing food using utensils already used to handle cow's milk (78.4%) stated that they were aware of the risk of cross-contamination. Conclusion: Caregivers of children diagnosed with CMPA still need more information to increase knowledge about nomenclatures and exclusion foods, in order to perform correct substitutions without risk of developing nutritional deficiencies.